2005
DOI: 10.1007/s00417-005-1164-3
|View full text |Cite
|
Sign up to set email alerts
|

Ocular manifestations in congenital toxoplasmosis

Abstract: At the end of the follow-up period, ocular involvement existed in 30% of the treated children with congenital toxoplasmosis. Associated eye pathologies were manifested less frequently than anticipated. They may occur later in life and are an indirect marker of the severity of congenital toxoplasmosis, but they do not have a direct impact on visual acuity. The overall functional prognosis of congenital toxoplasmosis is better than would be expected on the basis of literature findings, with only 2 of the 130 chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
2
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 21 publications
2
41
2
5
Order By: Relevance
“…Unlike this study which found only three cases of strabismus and no nystagmus, other studies have found higher cases of strabismus and nystagmus in ocular Toxoplama infection [14,17]. The development of strabismus and nystagmus seem to be associated with congenital cases as a result of disturbances of macular function during the developmental age.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Unlike this study which found only three cases of strabismus and no nystagmus, other studies have found higher cases of strabismus and nystagmus in ocular Toxoplama infection [14,17]. The development of strabismus and nystagmus seem to be associated with congenital cases as a result of disturbances of macular function during the developmental age.…”
Section: Discussioncontrasting
confidence: 86%
“…Another study from Indonesia found visual impairment and blindness to occur in 70 and 13.9% respectively in patients with ocular toxoplasmosis [14]. A study by Kodjikian et al [17] reported a lower prevalence (23%) of visual impairment in 130 ocular toxoplasmosis cases. The devastating visual outcome in ocular toxoplasmosis is highly associated with the preponderance of posterior pole lesions.…”
Section: Discussionmentioning
confidence: 99%
“…There have also been case reports of microphthalmia associated with other intrauterine infections such as varicella, Toxoplasma gondii, herpes simplex virus, and cytomegalovirus. [8][9][10][11] In addition, early assessment of hearing is particularly important to allow prompt intervention in the case of abnormality.…”
Section: Investigations and Screeningmentioning
confidence: 99%
“…The developing embryo may be exposed to maternal infections, such as TORCH infections (ie, toxoplasmosis, rubella, cytomegalovirus, and herpes simplex, and syphilis) [38][39][40][41] and lymphocyte choriomenigitis. 42 These may spread either by the haematogenous route or by ascending maternal genitourinary tract or even during the delivery process.…”
Section: Intrauterine Infectionsmentioning
confidence: 99%